The Modern Hyperinflation Cycle : Some New Empirical Regularities - Saboin, Jose (IMF Working Papers; Working Paper ;, 2018)
Using a database of up to 62 variables for 196 countries over 57 years, a hyperinflation cycle has been characterized to propose a broader setting of stylized facts. Beyond the usual facts, the findings in this paper contribute to the literature of modern hyperinflations in that these cycles occur in contexts where there are (i) depressed economic freedoms, (ii) deteriorated socioeconomic conditions and rule of law, as well as (iii) high levels of domestic conflictivity and government instability. Despite social infraestructure factors improve during stabilization, they keep being substantially lower than the respresentative non-hyperinflation country, suggesting an important role for them in the occurrence of modern hypeinflations. Finally, the role of international financial assistance in stabilization was studied, noting that (i) a clear majority of hyperinflation countries used it, further improving their (ii) economic freedoms, and allowing themselves (iii) greater fiscal flexibility and (iv) more exchange rate stability.